Analysis of six 'neuro‐enhancing' phenidate analogs. Issue 3 (March 2017) - Klare, Helge; Neudörfl, Jörg M.; Brandt, Simon D.; Mischler, Elisabeth; Meier‐Giebing, Sigrid; Deluweit, Kathrin; Westphal, Folker; Laussmann, Tim
Abstract : Six collected phenidates, i.e., 4‐methylmethylphenidate, 3, 4‐dichloromethylphenidate, ethylphenidate, 3, 4‐dichloroethylphenidate, ethylnaphthidate, and N‐ benzyl‐ethylphenidate were fully characterized by means of X‐ray, nuclear magnetic resonance (NMR), gas chromatography–mass spectrometry (GC–MS), electrospray ionization‐tandem mass spectrometry (ESI‐MS/MS), attenuated total reflectance Fourier transform infrared (ATR‐FTIR) and GC solid‐state IR analysis. Crystallography revealed the exclusive presence of the threo ‐configuration. Steric crowding induced by N‐ benzyl substitution at the piperidine moiety prompted an adoption of an unexpected axial positioning of substituents on the piperidine moiety in the crystal state as opposed to the exclusive equatorial positioning encountered in N ‐unsubstituted phenidate analogues. Gas phase computations of the relative lowest energy conformers confirm that the axial positioning appears to be favoured over the equatorial positioning; in solution, however, equatorial positioning is predominant according to nuclear Overhauser effect experiments. All samples, mainly originating from China, had a good to very good degree of purity indicative of their professional chemical synthesis. Routine analysis of these drugs by GC–MS revealed thermal decomposition of phenidate analogues in the injection port and/or on column to 2‐aryl‐ethyl‐acetates and 2, 3, 4, 5‐tetrahydropyridines. The decomposition pathway was suggested to proceed via a 6‐membered transition state which was supported by density functional theory (DFT) computations. Fragmentation pathways of decomposition products as well as the corresponding electron ionization (EI) mass spectra are provided. The thermal instability might thus render smoking or 'vaping' of these drugs a less effective route of administration. The analytical fingerprints of six structurally diverse phenidate analogues provide a helpful reference to forensic chemists in charge of identifying new psychoactive substances. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Six analogues of methylphenidate (Ritalin®) were analyzed and fully characterized by X‐ray, NMR, GC‐EI‐MS, ESI‐MS/MS and FTIR. Thermal decomposition of phenidates on column under routine GC–MS conditions was rationalized by experiment and DFT computations.